Weed Control in Sweet Corn - William M. Stall (EDIS)
Revised! HS-197, a 5-page fact sheet by William M. Stall, describes effective weed management practices for cultivation of sweet corn in Florida, and a table of chemical weed controls. Published by the UF Department of Horticultural Sciences, major revision April 2009.